Some Questions About Distance Learning and the Role of the University - W. Franklin Spikes (Educational Considerations, 1999)
One can easily argue that the world of higher education is a microcosm of today’s larger society. While colleges and universities have traditionally been organized around what some suggest are the rather ethereal pursuits of learning, teaching, and research, today’s campuses are increasing being challenged by the same intense, substantial and practical social issues that are present in the more broadly defined world that exists outside of their boundaries.